Arabica coffee–macadamia intercropping: Yield and profitability with mechanized coffee harvesting - Perdoná, Marcos J.; Soratto, Rogério P. [UNESP] (Wiley, 2020)
Arabica coffee (Coffea arabica L.)–macadamia (Macadamia integrifolia Maiden & Betche) intercropping presents benefits at the initial phase; however, coffee yields gradually decline because of shading, and mechanized coffee harvesting may be impeded by the growth of macadamia trees. An experiment was conducted under irrigated conditions in southeastern Brazil to evaluate whether coffee–macadamia intercropping and the use of pruning to allow mechanized coffee harvesting offers agronomic and economic advantages over continuously cropped coffee monoculture (monocropped coffee). In addition, we aimed to evaluate which macadamia cultivar (Hawaiian cultivars; HAES 344, HAES 660, and HAES 816; Brazilian cultivars: IAC 9–20, IAC 4–12B, and IAC 4–20) is most suitable for long-term intercropping with mechanized coffee harvesting. Hawaiian macadamia cultivars have a narrower canopy, requiring less pruning of the lateral branches to allow the traffic of the mechanical coffee harvester. The macadamia cultivar IAC 4–12B had the highest kernel yield and IAC 4–20 had the lowest yield. Because intercropped treatments have 33.3% fewer coffee plants and their production per plant was reduced by shading, the coffee yield in these treatments was on average 38% lower than that in monocropped coffee. However, due to the sale of the macadamia kernel, coffee–macadamia intercropping was economically superior to coffee monoculture. Depending on the macadamia cultivar, the economic benefit of intercropping was from 9% (IAC 4–20) to 206% (HAES 816 and IAC 4–12B) higher than that achieved with monocrop coffee cultivation.